1996
DOI: 10.1007/bf00211331
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine residues in tissues of striped dolphins affected by the 1990 mediterranean epizootic: Relationships with the fatty acid composition

Abstract: A simple and rapid method was developed for the simultaneous determination of fatty acids, organochlorine pesticides, and polychlorinated biphenyl (PCB) congeners in the same sample in order to explore possible connections between levels of contaminants and fatty acid composition. The method was applied to samples of melon, cerebrum, cerebellum, lung, liver, kidneys, and skeletal muscle obtained from 5 male and 5 female striped dolphins (Stenella coeruleoalba) found stranded in 1990 in the northeastern Spanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…Such decreases in desaturase activity can unfavorably alter the composition of n-3 PUFAs, such as EPA and DHA, which in turn can increase the risk of cardiovascular disease (Mozaffarian and Rimm, 2006). Our results are in accordance with previous animal and human studies (Grandjean and Weihe, 2003; Guitart et al, 1996; Matsusue et al, 1997, 1999). We also observed a concomitant increase in calculated Δ5 desaturase activity with increasing PCB exposure.…”
Section: Discussionsupporting
confidence: 94%
“…Such decreases in desaturase activity can unfavorably alter the composition of n-3 PUFAs, such as EPA and DHA, which in turn can increase the risk of cardiovascular disease (Mozaffarian and Rimm, 2006). Our results are in accordance with previous animal and human studies (Grandjean and Weihe, 2003; Guitart et al, 1996; Matsusue et al, 1997, 1999). We also observed a concomitant increase in calculated Δ5 desaturase activity with increasing PCB exposure.…”
Section: Discussionsupporting
confidence: 94%
“…1). This finding has been observed previously [13,[39][40][41] and may be attributed to the unique lipid composition of brain matter or the presence of the blood-brain barrier, a series of tightly joined endothelial cells at the brain:circulatory interface that impede the passage of polar solutes from blood into the brain. The lipid profile of brain tissue is dominated by phospholipids, which are more polar in comparison to the triacylglycerols composing blubber and melon [26].…”
Section: Statistics and Calculationsmentioning
confidence: 51%
“…In the striped dolphin, Kawai et al [26] observed that POP levels were highest in tissues with a high proportion of triacylglycerols, whereas tissues dominated by phospholipids and cholesterol exhibited lower POP concentrations. Furthermore, Guitart et al [39] detected correlations between contaminant concentrations and fatty acid composition of striped dolphin tissues. Tissue lipid composition, in addition to lipid content, may therefore play a role in determining the level of tissue-specific contaminant exposure.…”
Section: Tissue-specific Partition Coefficientsmentioning
confidence: 97%
“…Analyses of FAs were carried out as described previously7 , using the 13:0 FA as internal standard. For OC analysis, samples were concentrated to approximately 100 μΐ (never to dryness) under a gentle stream of N 2 prior to injection in the gas Chromatograph.…”
mentioning
confidence: 99%